PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMA PADA MATERI GERAK HARMONIK SEDERHANA - Ince Raudhiah Zahra; Benyamin Matius; Abdul Hakim (Vidya Karya, 2018)
Abstract. This study aims to determine the improvement of student’s problem solving skill after applying the problem based learning model and determine it’s effectiveness. This is a quantitative research with one group pretest-posttest design. Cluster random sampling was used, and 28 samples were obtained from one of high schools in Samarinda. The result of the analysis with Wilcoxon Signed Rank Test. The result showed that there’s a significant difference between students’ problem solving skill before and after the treatment, with the p-value 0,00 with significance 0,05. Generally, students’ problem solving skill increased from 8.5 to 29.5, with N-Gain of 0,2, which is classified as a low category. The highest gain was found in the ability of understanding the problem, with the N-Gain of 0,4, which is classified as a middle category. Meanwhile the indicator of students’ skill on planning problems, solving problems, and doing the re-check, were classified as low increasing category with N-Gain of 0,2. Based on calculation of effect size (d), which is 1,96 that is classified as a big category, the implementation of the treatment had a high effectiveness.   Keywords : Problem Based Learning, Problem Solving Skill, Simple Harmonic MotionAbstrak. Penelitian ini bertujuan untuk mengetahui peningkatan kemampuan pemecahan masalah siswa setelah diterapkan model problem based learning dan mengetahui tingkat efektifitas dari penerapan model tersebut. Penelitian ini merupakan penelitian kuantitatif dengan desain one group pretest-posttest. Teknik pengambilan sampel yang digunakan adalah cluster random sampling, dengan sampel sebanyak 28 siswa dari salah satu sekolah SMA di Samarinda. Data dianalisis menggunakan Wilcoxon Signed Rank Test. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara kemampuan pemecahan masalah siswa saat pretest dan posttest dengan perolehan p-value 0,00 dan signifikansi 0,05. Rata-rata kemampuan pemecahan masalah siswa mengalami kenaikan dari 8,5 menjadi 29,5 dengan N-Gain 0,2 yang termasuk dalam kategori rendah. Peningkatan tertinggi diperoleh indikator memahami masalah dengan N-Gain 0,4 yang termasuk dalam kategori sedang, sedangkan indikator kemampuan siswa merencanakan masalah, menyelesaikan masalah dan melakukan pengecekkan kembali termasuk dalam kategori rendah dengan N-Gain 0,2. Tingkat efektivitas yang diperoleh termasuk dalam kategori tinggi dengan nilai effect size (d) 1,96 yang termasuk dalam kategori besar.Kata Kunci : Problem Based Learning, Kemampuan Pemecahan Masalah, Gerak Harmonik Sederhana